Effect of Work Discipline and Employee Training in the State Power Plant Distribution Corporation of West Java and Banten on Employee Performance - Rohendra, Titto (CENTRAL ASIA AND THE CAUCASUS, 2022)
The company's attention to employee performance is very high, as well as the West Java and Banten State Electricity Distribution Companies are concerned about the problems that occur in the performance of their employees. This corporation has three standards in determining the performance of its employees, namely SAIDI, SAIFI, and Distribution of Loss. The main problem with the performance of employees in this company is that it fluctuates every year and the average is always below that standard. Factors that affect employee performance include compensation, leadership, work motivation, work discipline, and other factors. The purpose of this study was to analyze the effect of work discipline and training on employee performance in the company. Researchers carry out application research with a verification research design through a quantitative approach. The sampling technique used is Proportionate Stratified Random Sampling. Data processing is done by path analysis. The results showed that work discipline and job training had an effect on employee performance.